Influence of shock wave/boundary layer interaction on condensation flow and energy recovery in supersonic nozzle. (15th January 2023) - Liu, Yang; Cao, Xuewen; Guo, Dan; Cao, Hengguang; Bian, Jiang
Abstract: Shock train phenomenon occurs when the Mach number increases during the process of energy recovery in the nozzle. However, the reduction of wet natural gas purification efficiency and the increase in energy loss can be caused by shock wave in the supersonic separator. This study focused on the condensation characteristics and pressure energy recovery efficiency under the shock train in the Laval nozzle. A mathematical model was developed for the process of methane-water vapour supersonic condensation and verified by condensation experiments. The results demonstrate that the length of the boundary layer separation interval can be reduced by 0.142 m with a decrease of 0.909 upstream Mach number from 2.367 to 1.458. Multiple nucleation of vapour occurs under the effect of shock train. The droplet growth interval increases from 0 to 0.0859 m and the liquid mass fraction enhances from 0 to 0.12% as the pressure energy recovery efficiency decreasing from 80% to 30%. This indicates that the suitable pressure energy recovery efficiency from 40% to 60% can effectively control the location of the shock train and organize its structure in the nozzle to reduce the separation length of boundary layer and improve the nozzle liquefaction efficiency. Graphical abstract: Image 1 Highlights: Shock train phenomenon during pressure energy recovery in Laval nozzle was observed. Length of boundary layer separation reduced with a decrease in upstream Mach number. Multiple nucleation and evaporation of water vapour with shock train were studied. Low back pressure achieved higher liquefaction efficiency with more energy loss.